A descent generalized RMIL spectral gradient algorithm for optimization problems - Sulaiman, Ibrahim M.; Kaelo, P.; Khalid, Ruzelan; Nawawi, Mohd Kamal M. (Zielona Góra: Uniwersytet Zielonogórski)
This study develops a new conjugate gradient (CG) search direction that incorporates a well defined spectral parameter while the step size is required to satisfy the famous strong Wolfe line search (SWP) strategy. The proposed spectral direction is derived based on a recent method available in the literature, and satisfies the sufficient descent condition irrespective of the line search strategy and without imposing any restrictions or conditions.
Keywords: optimization models; spectral CG algorithm; global convergence; line search strategy